2013
DOI: 10.1016/j.gca.2013.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of rates and mechanisms of isotope exchange (O, H) between volcanic ash and isotopically-labeled water

Abstract: The hydrogen and oxygen isotope ratios in hydrous minerals and volcanic glass are used as paleo-proxies to infer isotopic values of meteoric waters and thus paleoclimate conditions. Long-term exposure experiments with Mt Mazama ash reacted with isotopically labeled water (+650‰

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…We do note that a very few ORP within pumice do resemble those present after the hightemperature experimental runs (e.g., Figure S4 compared with Figures 9b,c). 6) Using fractionation factors from Kita et al (1985), the observed range of 20 ± 8‰ δ 18 O is consistent with formation of amorphous silica from meteoric water at 20 • C, or with the heavier Kawah Ijen lake water (or magmatic water) at more elevated temperatures around 100-150 • C. The low δD is consistent with dehydration and loss of H 2 O from the opal at some point after initial formation as D is preferentially lost during silicate devolatilization (Dobson et al, 1989;Nolan and Bindeman, 2013). It is possible that a more detailed in-situ study of stable isotopes might identify multiple populations of opaline materials formed under disparate conditions.…”
Section: Discussion Primary Observationsmentioning
confidence: 64%
See 1 more Smart Citation
“…We do note that a very few ORP within pumice do resemble those present after the hightemperature experimental runs (e.g., Figure S4 compared with Figures 9b,c). 6) Using fractionation factors from Kita et al (1985), the observed range of 20 ± 8‰ δ 18 O is consistent with formation of amorphous silica from meteoric water at 20 • C, or with the heavier Kawah Ijen lake water (or magmatic water) at more elevated temperatures around 100-150 • C. The low δD is consistent with dehydration and loss of H 2 O from the opal at some point after initial formation as D is preferentially lost during silicate devolatilization (Dobson et al, 1989;Nolan and Bindeman, 2013). It is possible that a more detailed in-situ study of stable isotopes might identify multiple populations of opaline materials formed under disparate conditions.…”
Section: Discussion Primary Observationsmentioning
confidence: 64%
“…% H 2 O with a TCEA-MAT 253 system at the University of Oregon Stable Isotope Lab as discussed by Nolan and Bindeman (2013). The δ 18 O analyses of bulk perlite was performed in 1-2 mg quantities using laser fluorination using a home-built airlock chamber allowing analysis of a single sample without prefluorinating other samples.…”
Section: Methodsmentioning
confidence: 99%
“…Describing the complex adsorption of water before TGA and its desorption during TGA is beyond the scope of this study. Adsorbed water consists of layers of water molecules that are attached to the glass surface, the first layer being bonded to the grain via Si-O bonds and subsequent layers of water molecules being attached through a network of hydrogen bonds between individual water molecules (e.g., Garofalini, 1990;Christy, 2010;Nolan and Bindeman, 2013). It has already been shown that during TGA the loss of adsorbed water occurs at lower temperatures than the loss of magmatic water, mainly because of its geometrical position on the external surface of each grain and its speciation (e.g., Newman et al, 1986;Westrich, 1987;Sodeyama et al, 1999;Roulia et al, 2006).…”
Section: Adsorbed Watermentioning
confidence: 99%
“…For example, the D/H ratio of meteoric water is distinct from magmatic water (e.g., DeGroat-Nelson et al, 2001;Harford et al, 2003;Tuffen et al, 2010). However, Nolan and Bindeman (2013) showed that the D/H ratio can be rapidly changed by minor diagenesis, even at relatively low temperatures of 20°C (and despite no significant water gain after 2 years at 70°C was observed), making its interpretation complicated. Among the different methods available to distinguish magmatic from secondary water, oxygen isotopes may be the most reliable technique (Goff and McMurtry, 2000;Tuffen et al, 2010;Nolan and Bindeman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Product H 2 and CO gases were separated in a gas chromatograph and analyzed by CF‐IRMS. Since then, many researchers have adapted their method for hydrogen‐isotope analysis of closed‐system fluids, freshwater chert, silicic magmas, and various hydrous minerals . Nine of these studies used NBS 30 biotite as one of the RMs.…”
Section: Selected Hydrogen‐isotope Measurements Of Nbs 30 Biotitementioning
confidence: 99%